PHYSICAL CHARACTERIZATION AND SUNSCREEN ACTIVITY OF NUTMEG OIL NANOEMULSION WITH ISOPROPYL MYRISTATE VARIATIONS - Siti Setianingsih; Rizky Adityo Saputro; Vironica Rizky Fauziah; Wahyu Setyo Wibowo; Ayu Shabrina (Jurnal Farmasi Sains dan Praktis, 2023)
The nutmeg seed oil contains myristicin which can absorb UV rays. Nanoemulsion with isopropyl myristate can be used to increase the activity of sunscreen. This study aimed to determine the physical characteristics and effectivity of nutmeg oil (NMO) nanoemulsion with isopropyl myristate as an enhancer. The nanoemulsion was made with 6.4% NMO and variations of isopropyl myristate 1% (FI), 3% (FII), and 5% (FIII). The nanoemulsions were evaluated for physical characteristics such as appearance, pH, viscosity, transmittance percentage, particle size, and polydispersity index (PI). The in vitro SPF value was tested using a spectrophotometer, and sunscreen effectivity was determined by the Minimum Erythemal Dose (MED) value. Data obtained were analyzed using one-way ANOVA. This study showed that the colour of the NMO nanoemulsion was light yellow and clear, with a transmittance percentage of 97.5-97.9%. The pH FI, FII, and FIII results were 6.79±0.03, 6.84±0.04, and 7.02±0.03. The viscosity was 1.63 ± 0.81 to 1.82 ± 0.85 d.Pas with Newtonian rheology. The particle size was 14.3 ± 1.41 nm to 16.0 ± 2.13 nm, with PI less than 0.5. SPF value were 16.34 ± 5.50 (FI); 16.70 ± 5.20 (FII) and 17.80 ± 3.20 (FIII). MED values were 220.5 ± 6.34 (FI), 225.4 ±5.41 (FII), and 240.2 ±3.45 (FIII) minutes. The MED value showed that FIII was significantly different from FI and FII. Isopropyl myristate at 5% in nanoemulsion increases the effectivity of sunscreen.